Impact of interest rate differential, exchange rate changes and political stability on Foreign capital inflow in Nigeria: Discrete threshold regression model - Joseph Chukwudi Odionye; Ethelbert Ukachukwu Ojiaku; Chiwuike N. Uba (Cogent Economics & Finance, 2023)
Lack of investable capital has slowed down the development process in many developing nations, including Nigeria, and this has sparked empirical research on the factors affecting foreign capital flow. Therefore, the purpose of this study was to investigate the effects of interest rate differential, exchange rate changes, and political stability on the entrance of foreign capital into Nigeria between 1981 and 2021. To investigate the impact of the factors on foreign capital inflow in regimes with low and high interest rate differentials, the study used a discrete threshold regression model (DTRM). The study discovered an interest rate differential threshold value of 3.68 percent, indicating that an interest rate differential high and over the predefined threshold promotes a favorable and considerable inflow of foreign capital into the nation. Additionally, the country's capital inflow is influenced by political stability and exchange rate fluctuations. The implication is that investors evaluate a country's IRD in relation to other risk factors (political and macroeconomic) and will only invest if the IRD is higher than3.68 percent since it will balance out other opportunity costs at home and risk factors in the receiving country's economy.
Keywords: C22; C35; F21; G15; 330; Discrete threshold regression; exchange rate; foreign capital flow; interest rate differential; political stability